First record of Euphorbia pedersenii Subils (Euphorbiaceae) for Brazil - Külkamp, Josimar; Da Silva, Otávio Luis Marques; Valduga, Eduardo; Iganci, João Ricardo Vieira; Cordeiro, Inês; Baumgratz, José Fernando A. (Phytotaxa, 2018)
We report the first record of Euphorbia pedersenii (Euphorbiaceae) for Brazil, a rare species previously known from a few localities in Argentina. The species belongs to Euphorbia sect. Nummulariopsis and is characterized by its small habit with a well-developed tuberous root system, usually linear leaves, trapezoidal cyathial glands, and pubescent ovary and fruit. In the state of Rio Grande do Sul it grows in open grasslands of the Pampa region, a phytogeographic domain severely impacted by agriculture. We provide an assessment of the conservation status and geographical distribution and habitat of E. pedersenii, along with an identification key to the species of sect. Nummulariopsis occurring in Brazil.